Analisis Aturan dan Pengelolaan Badan Usaha Milik Desa Berupa Sumber Daya Pariwisata Pantai di Greenthing Beach - Sulistina; Nurtoyyiba, Rifka; Silhatunnayati, Rian; Firliyani, Zulfa (Indra Institute Research & Publication, 2025)
The management of Village-Owned Enterprises is a manifestation to improve the economic level of the village and the surrounding community. Therefore, its management must be based on the principles of openness and community participation. The purpose of this study was to determine the legal basis for economic development in the village, and to analyze the implementation of the Right to Control Coastal Resources, especially those based on the people's economy. The research method used is empirical juridical. The results of the study are the legal umbrella of BUMDesa in laws and regulations, including: The Legal Basis for Economic Development in the Village is stated in several laws and regulations in Indonesia; The right to control coastal resources is a manifestation to maximize village potential. This concept is intended to improve the welfare of the community, especially around the coastal area; Resources Based on the People's Economy in the Management of Greenthing Beach Tourism have been based on the people's economy. This is based on the condition of the tourism location that is in accordance with the needs and potential of the village as an effort to improve community welfare. Greenthing beach is managed by BUMDes and is a pillar of economic activity that functions as a social and commercial institution that is run with the principles of cooperative, participatory, transparent, emancipatory, accountable, and sustainable.